ROLE OF DICTION ON THE PRACTICALITY OF THE EDUCATION MODULE ISLAMIC RELIGION WITH ANTI-RADICALISM AND TERRORISM NUANCES - Febrina Riska Putri; Syahrizal Syahrizal; Weni Yulastri (ppjbsip, 2020)
Modules can be used independently in learning by students. The Antiradicalism and Terrorism Islamic Religious Education Module is a module intended for PGRI West Sumatra teacher and tertiary high school students, specifically and specifically for students throughout Indonesia who need learning resources in Islamic Religious Education lectures at General Higher Education. This module is expected to assist students in studying Islamic Religious Education courses, according to the material needed in the module so that it can be used in real life in the midst of society. The module is a module that is easily made by students because the module is a learning tool that students can use independently in learning. This module is well equipped to meet Indonesian grammar, in this case the choice of words or diction used is important to support the practicality of student understanding. Based on the results of using the usage module, this module has been approved practically. This is inseparable from the important role of grammar and data choices or diction used.AbstrakModul dapat digunakan secara mandiri dalam pembelajaran oleh siswa. Modul Pendidikan Agama Islam Antiradikalisme dan Terorisme adalah modul yang diperuntukkan bagi guru dan siswa SMA PGRI Sumatera Barat, secara khusus dan khusus bagi siswa di seluruh Indonesia yang membutuhkan sumber belajar dalam perkuliahan Pendidikan Agama Islam di Perguruan Tinggi Umum. Modul ini diharapkan dapat membantu mahasiswa dalam mempelajari mata kuliah Pendidikan Agama Islam, sesuai dengan materi yang dibutuhkan dalam modul agar dapat digunakan dalam kehidupan nyata di tengah-tengah masyarakat. Modul merupakan modul yang mudah dibuat oleh siswa karena modul merupakan sarana pembelajaran yang dapat digunakan siswa secara mandiri dalam pembelajaran. Modul ini dilengkapi dengan baik untuk memenuhi tata bahasa Indonesia, dalam hal ini pemilihan kata atau diksi yang digunakan penting untuk mendukung kepraktisan pemahaman siswa. Berdasarkan hasil penggunaan modul penggunaan, modul ini telah disetujui secara praktis. Hal ini tidak terlepas dari peran penting tata bahasa dan pilihan data atau diksi yang digunakan